The youth football journey: parents' experiences and recommendations for support. Issue 6 (2nd November 2021) - Newport, Rachael A.; Knight, Camilla J.; Love, Thomas D.
ABSTRACT: The purpose of this study was to understand parents' experiences and offer recommendations for supporting parents within youth academy football. The lead researcher was embedded within a football academy for 8 months and collected data through 29 formal interviews, three focus groups, observations, informal conversations, and field notes. Data were analysed using reflexive thematic analysis. Overall, analysis of the data indicated that, while their son was in the academy, parents experience a journey that consists of four individual phases; 1) excited and amazed, 2) dawning of reality, 3) accepting and rationalising, and 4) focusing on the future. Two overarching themes were also present throughout the journey; 1) enjoyment, opportunity, and development, and, 2) sacrifices, commitment, and consequences on personal life. To support parents through these phases, informational and social support, along with cultural changes would be useful. Specifically, parents may benefit from a parent supportive culture in which they are welcomed, respected, and valued, combined with a programme of specific support sessions. Overall, the findings illustrate the complexity of the football academy parent journey and the importance of those providing support to understand parents' journeys and tailor support to their specific needs.